2003
DOI: 10.1590/s0365-05962003000300002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina C

Abstract: Há muito o papel do ácido ascórbico (AA) no metabolismo do tecido conjuntivo tem sido reconhecido, sobretudo a partir do século 16, quando o escorbuto começou a ser prevenido com sumo de frutas cítricas. As primeiras publicações referentes ao uso tópico da vitamina C, inicialmente em cobaio, datam da década de 1960. Entretanto, só mais recentemente tem-se dado valor a essa via de aplicação. Os autores apresentam revisão sobre o assunto, discorrendo sobre o histórico da vitamina C, seus efeitos no metabolismo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
0
17
0
29
Order By: Relevance
“…One classic example concerns the consumption of citrus fruit, scurvy in 18 th century seafarers, and vitamin C. 1,2 Sir Walter Haworth and Albert von Szent-Gyorgyi were awarded the 1937 Nobel Prize for their work in identifying vitamin C. 3,4 Through food guidelines responsive to recommended daily allowances of nutrients, food has appropriately remained the primary agent in the practice of scurvy prevention; however, this science was eventually commercialized with the production of purified vitamin C, and the use of vitamin C as a nonfood supplement is currently popular. 4 Behind those early events rests a multitude of pathways for the development of nutrition science and practice. 5 This review argues for the need to build the science base on foods because a focus on nutrients tends to oversimplify a complex system and has even done harm.…”
Section: Introductionmentioning
confidence: 99%
“…One classic example concerns the consumption of citrus fruit, scurvy in 18 th century seafarers, and vitamin C. 1,2 Sir Walter Haworth and Albert von Szent-Gyorgyi were awarded the 1937 Nobel Prize for their work in identifying vitamin C. 3,4 Through food guidelines responsive to recommended daily allowances of nutrients, food has appropriately remained the primary agent in the practice of scurvy prevention; however, this science was eventually commercialized with the production of purified vitamin C, and the use of vitamin C as a nonfood supplement is currently popular. 4 Behind those early events rests a multitude of pathways for the development of nutrition science and practice. 5 This review argues for the need to build the science base on foods because a focus on nutrients tends to oversimplify a complex system and has even done harm.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the vitamin C content decreased from day 7 to day 60 in all the treatments, except for KHP-I. This was due to the degradation of vitamin C in the presence of light and/or oxygen during the preparation of the analysis [35].…”
Section: Level Of Vitamin C and Antioxidant Activitymentioning
confidence: 77%
“…19 It was demonstrated that ascorbic acid promotes the synthesis of mature and normal collagen through the perfect maintenance of the activity of the enzymes lysyl hydroxylase and prolyl hydroxylase. 19,20 In an intracellular environment these enzymes catalyze the hydroxylation of some lysine and proline residues in the collagen polypeptides, enabling the formation and stabilization of the collagen triple helix. 19,21 Franceschi et al.…”
Section: Discussionmentioning
confidence: 99%